Corporate Point of View in Green Accounting - Setiani P. Hendratno (Bina Nusantara University, 2016)
The purpose of this research was to find out the influence of view attention, responsibility, reporting accounting environment, and audit environment to see the importance of green accounting on employees who worked in Tangerang related to the problem of the environment in the company. The research population consisted of all employees of the company. The eligible questionnaires were given to 108 respondents. Data collection was using questionnaires. The data were analyzed using the regression test with analysis tools STATA 12. The result indicates that the variable attention in the environment, responsibility in the environment, and environmental accounting report gives impact on the point of view of the importance of green accounting in a company.